Dermoscopy and the diagnosis of primary cutaneous B‐cell lymphoma. (12th September 2017) - Geller, S.; Marghoob, A.A.; Scope, A.; Braun, R.P.; Myskowski, P.L.
Abstract: Background: Primary cutaneous B‐cell lymphomas (PCBCLs) are frequently misdiagnosed, and a biopsy is needed to attain the correct diagnosis. Objective: To characterize the dermoscopic features of PCBCL. Methods: In this retrospective observational study, we analysed the pathology reports of 172 newly diagnosed PCBCL for the initial clinical differential diagnosis. The dermoscopic images of 58 PCBCL were evaluated for dermoscopic features. Two dermoscopy experts, who were blinded to the diagnosis and the study objective, evaluated images from 17 cases for a dermoscopic differential diagnosis. Results: Of 172 biopsy‐proven PCBCL lesions, cutaneous lymphoma was suspected by the clinician in 16.3%; the leading diagnosis was basal cell carcinoma in 17.4%, and other skin neoplasms in 21%. Studying 58 PCBCL dermoscopic images, we most frequently identified salmon‐coloured background/area (79.3%) and prominent blood vessels (77.6%), mostly of serpentine (linear‐irregular) morphology (67.2%). Dermoscopic features did not differ significantly by subtype or location. Blinded evaluation by dermoscopy experts raised a wide differential diagnosis including PCBCL, arthropod bite, basal cell carcinoma, amelanotic melanoma and scar/keloid. Conclusions: Two dermoscopic features, salmon‐coloured area/background and serpentine vessels, are frequently seen in PCBCL lesions. These characteristic dermoscopic features, although not specific, can suggest a possible diagnosis of PCBCL.